Synthesis and Characterization of Hydroxyapatite Composites Based on Tutut (Belamya Javanica) and Magnetite by Coprecipitation as Adsorbents of Pb Metals Ion - Charlena; Nazriati; Marita Soebrata, Betty; Dicky Iswara, Muhammad (Science and Technology Indonesia, 2025)
Increased industrial activity can result in the emission of pollutants into the environment, such as heavy metals, which are a significant source of concern. A practical approach to reduce this problem is to utilize Pb metal adsorption. This study aims to synthesize HAp from Bellamya javanica clam shells and characterize the HAp-Fe3O4 composite as a Pb metal ion adsorbent. FTIR and XRD analysis results showed the successful fabrication of the composite, resulting in a crystal dimension of 7.63 nm and a crystallinity level of 84.80%. SEM characterization showed a porous structure with a particle size of 10.98 um. Adsorption studies of Pb(II) ions showed that the HAp-Fe3O4 composite efficiently adsorbed Pb(II) ions, with the adsorption efficiency increasing from 95.80% to 98.40%. The adsorption isothermal model of the HAp-Fe3O4 composite follows the Freundlich model with a 1/n value of 0.31 and a KF value of 25.35 L/g. The adsorption kinetics study of the HAp-Fe3O4 composite follows the pseudo second-order model with an R2 value of 1, and the thermodynamic study shows the Gibbs free energy is negative, which indicates that the adsorption process is thermodynamically optimal and spontaneous. In addition, the enthalpy value is positive, indicating that the interaction between the adsorbent and lead ions is endothermic, and the entropy is negative, indicating the reduction of random collisions of lead ions in the solid (adsorbent) and aqueous solution during adsorption.